DISIPLIN KERJA PEMANEN KELAPA SAWIT DI PT. HARAPAN SAWIT LESTARI CARGILL KETAPANG - Chaerul Aziz Fatoni; Dewi Kurniati; Anita Suharyani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
PT. Harapan Sawit Lestari Cargill still has undisciplined workers. The purpose of this study was to determine the level of work discipline and the factors that influence the Work Discipline of Oil Palm Harvesters at PT. Harapan Sawit Lestari Cargill Ketapang. The method used in this research is a descriptive quantitative method using 100 respondents taken by positive sampling and data analysis used is Structural Equation Modeling (SEM) Lisrell software 8.80. The results are the level of discipline of oil palm harvest workers at PT. Harapan Sawit Lestari Cargill Ketapang is categorized as good. Variables that influence discipline are the leader justice retribution and firmness. PT. Harapan Sawit Lestari Cargill Lestari must pay attention to the level of labor discipline by conducting direct supervision. The foreman must be more assertive and fair to undisciplined workers who are given punishment or sanctions to provide a deterrent effect. Workers who obey the rules are given rewards in bonuses to motivate other workers not to violate. Treatment of workers must provide health facilities in adequate health insurance.